2011
DOI: 10.1212/wnl.0b013e3182315a33
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B12, cognition, and brain MRI measures

Abstract: Methylmalonate, a specific marker of B12 deficiency, may affect cognition by reducing total brain volume whereas the effect of homocysteine (nonspecific to vitamin B12 deficiency) on cognitive performance may be mediated through increased white matter hyperintensity and cerebral infarcts. Vitamin B12 status may affect the brain through multiple mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(68 citation statements)
references
References 36 publications
3
54
0
4
Order By: Relevance
“…We cannot extrapolate this to persons who already have cognitive problems. Furthermore, cross-sectional and prospective MRI studies, 36,37 as well as one RCT in patients with MCI, 38 observed beneficial effects of these vitamins on brain atrophy. To unravel the effects of B vitamins, a closer look into early brain pathologies would be useful to uncover subtle effects that are difficult to detect with paper and pencil tests.…”
Section: Cognitive Tests Cognitive Performance Was Assessed At Baselinementioning
confidence: 99%
“…We cannot extrapolate this to persons who already have cognitive problems. Furthermore, cross-sectional and prospective MRI studies, 36,37 as well as one RCT in patients with MCI, 38 observed beneficial effects of these vitamins on brain atrophy. To unravel the effects of B vitamins, a closer look into early brain pathologies would be useful to uncover subtle effects that are difficult to detect with paper and pencil tests.…”
Section: Cognitive Tests Cognitive Performance Was Assessed At Baselinementioning
confidence: 99%
“…7,8 In a cross-sectional study on an elderly population, a reduction in brain volume was observed with B 12 deficiency. 9 There are isolated reports of brain demyelination in patients with SACD, which may or may not show resolution following vitamin B 12 replacement. 10,11 Elderly populations with vitamin B 12 deficiency are reported to show whole-brain atrophy and white matter damage.…”
mentioning
confidence: 99%
“…Iron maldistribution reduces iron availability in the circulation, increase susceptibility to opportunistic infections and accelerate disease progression. 42 Treating severe anemia in HIV-infected patients is critical because recovery from anemia is associated with increased length of survival, however, excess of iron in the storage sites is associated with an increased viral replication. 43 The SBLS contains large amounts of iron and as such it is used in the treatment of anemia.…”
Section: Mineral Contents In Sblsmentioning
confidence: 99%